Detemination of alpha decay probability of 238U, 234U, 239Pu, 241 Am isotopes - Le, Chung Xuan; Tran, Hao Viet Nhan; Pham, Hung Quoc; Vu, Mai Thanh (VNU Journal of Science: Mathematics - Physics; Vol 20 No 3AP, 2017)
Abstracts